Pre-Processing for Text Extraction System using Histogram Techniques - Shiyamala, S; Suganya, S (International Journal of Computer Sciences and Engineering, 2025)
Now a days researchers are using natural images for their research work. Natural images contain text also. Text in natural images typically adds meaning to an object or scene. So extract the text from natural images is very important for applications which are processing with text. However, variations of text due to differences in size, style, orientation, and alignment, as well as low image contrast and complex background make the problem of automatic text extraction extremely challenging. Extracting text from an image can be done with image processing which deals with digital images. Extraction of text involves in different stages. They are named as preprocessing, detection, localization, extraction and recognition of the text from a given image. The aim of pre-processing is an improvement of the image data that suppresses unwanted distortions or enhances some image features important for further processing. So pre-processing is important stage to improve the image quality. This paper presents the existing histogram techniques for preprocessing and proposed a new technique named enhanced CLAHE which gives best contrast enhancement for natural scene images with text.